PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN TIKET MASKAPAI PENERBANGAN DOMESTIK DI DAVINA TOUR AND TRAVEL GORONTALO - Andari, Rini; Napu, Della Maghfira (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
Davina Tour and Travel is one of the travel agents in Gorontalo city which has over four years of experience, serving a variety of business market share in tour travel. From year to year the number of domestic airline ticket purchase is increasing. Every year the Tour and Travel Davina always target purchase amount must be heightened, but in the year 2013 to 2014 has decreased the number of domestic airline ticket purchases. Decreasing the amount of the airline ticket purchase in 2014 due to the wishes and needs of its customers and the fierce competition among travel agents in the city of Gorontalo, Davina Tour and Travel doing word of mouth (word of mouth promotion) as effort to increase the number of ticket purchase domestic airlines. This research aims to reveal the word of mouth and purchasing decisions as well as word of mouth influence on purchasing decisions. This type of this research using descriptive and verification, used explanatory survey method and cross sectional approach. Sample in this research were 100 respondents, travelers who purchase airline tickets for domestic flights in Davina Tour and Travel with the sampling technique used is simple random sampling. Data analysis technique used is multiple regression. The independent variable in this research is the word of mouth (X) consisting of cognitive content (X1), richness of content (X2) and the strength of delivery (X3) while the dependent variable is the purchasing decision (Y) which is composed of indicators product choice, brand choice, dealer choice, purchase timing, purchase amount and payment method. Tourist’s responses to word of mouth in Davina Tour and Travel considered sufficient high. Richness of content dimension to obtain the highest value whiles the cognitive content dimension to obtain the lowest value. Tourist’s responses on purchasing decisions in Davina Tour and Travel considered sufficient high. Indicators of brand choice to obtain the highest value and the number of purchase to obtain the lowest value. Based on SPSS 20.0 for Windows testing showed that simultaneous and partial effect between word of mouth and purchasing decisions. The advice for company is improving communication with the sender of the WOM message and expressed positive messages and attractive so as to generate interest message recipients to buy airline tickets for domestic flights in Davina Tour and Travel.